2018
DOI: 10.1177/0954410018795806
|View full text |Cite
|
Sign up to set email alerts
|

A fast multiobjective optimization approach to S-duct scoop inlets design with both inflow and outflow

Abstract: A fast multiobjective optimization method for S-duct scoop inlets considering both inflow and outflow is developed and validated. To reduce computation consumption of optimization, a simplified efficient model is proposed, in which only inflow region is simulated. Inlet pressure boundary condition of the efficient model is specified by solving an integral model with both inflow and outflow. An automated optimization system integrating the computational fluid dynamics analysis, nonuniform rational B-spline geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Furthermore, according to previous studies, Rodriguez 17 used k-ω SST turbulence model to predict distortion of L-inlet duct for the design of Siemens gas turbine, which was proven by engineering application. Fiola 25 and Zeng 7 found that k-ω SST turbulence model can predict the separation flow well with the experimental data. Compared to the k-ε RNG model, the k-ω SST model is known for its improved numerical stability nearby the wall.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Furthermore, according to previous studies, Rodriguez 17 used k-ω SST turbulence model to predict distortion of L-inlet duct for the design of Siemens gas turbine, which was proven by engineering application. Fiola 25 and Zeng 7 found that k-ω SST turbulence model can predict the separation flow well with the experimental data. Compared to the k-ε RNG model, the k-ω SST model is known for its improved numerical stability nearby the wall.…”
Section: Methodsmentioning
confidence: 73%
“…The Sshaped bend design which has been investigated a lot is the typical prototype of aero-engine inlet. [4][5][6][7] On the other hand, the L-shaped bend design is widely used in ground gas turbine inlet and marine gas turbine inlet due to the constraint of space layout that minimum space and avoidance of inhaling ground particles are required. The L-inlet duct would not only increase the pressure drop, but also aggravate the flow distortion, which may reduce the efficiency and cause surge in some severe conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Baals et al [70] and Nichols et al [71] provided a detailed study of the effect of inlet lip geometry on aerodynamic performance. They reported that the NACA 1-series airfoils provide good performance by delaying sonic and separated flow for a large span of duct-to-flight-velocity ratios and Ma numbers [70][71][72][73]. Furthermore, Re [74] studied the aerodynamic performance of various NACA 1-series inlets and concluded that the inlet critical Ma number depends on the lip shape [74,75].…”
Section: X-45 X-47bmentioning
confidence: 99%